Digital Immunophenotyping Predicts Disease Free and Overall Survival in Early Stage Melanoma Patients - Francesco De Logu; Francesca Galli; Romina Nassini; Filippo Ugolini; Sara Simi; Mara Cossa; Clelia Miracco; Andrea Gianatti; Vincenzo De Giorgi; Eliana Rulli; Antonio Cossu; Daniela Massi; et al. (Cells, 2021)
Background: the prognostic significance of tumor infiltrating lymphocytes (TILs) in intermediate/thick primary cutaneous melanoma (PCM) remains controversial, partially because conventional evaluation is not reliable, due to inter-observer variability and diverse scoring methods. We aimed to assess the prognostic impact of the density and spatial distribution of immune cells in early stage intermediate/thick PCM. Materials and Methods: digital image acquisition and quantitative analysis of tissue immune biomarkers (CD3, CD4, CD8, CD68, PD-L1, CD163, FOX-P3, and PD-1) was carried out in a training cohort, which included patients with primary PCM ≥ 2 mm diagnosed, treated, and followed-up prospectively in three Italian centers. Results were validated in an independent Italian cohort. Results: in the training cohort, 100 Stage II–III melanoma patients were valuable. At multivariable analysis, a longer disease free survival (DFS) was statistically associated with higher levels of CD4+ intratumoral T-cells (aHR [100 cell/mm2 increase] 0.98, 95%CI 0.95–1.00, p = 0.041) and CD163+ inner peritumoral (aHR [high vs. low] 0.56, 95%CI 0.32–0.99, p = 0.047). A statistically significant longer DFS (aHR [high-high vs. low-low] 0.52, 95%CI 0.28–0.99, p = 0.047) and overall survival (OS) (aHR [high-high vs. low-low] 0.39, 95%CI 0.18–0.85, p = 0.018) was found in patients with a high density of both intratumoral CD8+ T-cells and CD68+ macrophages as compared to those with low density of both intratumoral CD8+ T-cells and CD68+ macrophages. Consistently, in the validation cohort, patients with high density of both intratumoral CD8+ and CD3+ T-cells were associated to a statistically better DFS (aHR[high-high vs. low-low] 0.24, 95%CI 0.10–0.56, p < 0.001) and those with high density of both intratumoral CD8+ and CD68+ were associated to a statistically longer OS (aHR[high-high vs. low-low] 0.28, 95%CI 0.09–0.86, p = 0.025). Conclusion: our findings suggest that a specific preexisting profile of T cells and macrophages distribution in melanomas may predict the risk of recurrence and death with potential implications for the stratification of stage II–III melanoma patients.